1975
DOI: 10.1111/1523-1747.ep12512337
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lipid Composition of Isolated Human Sebaceous Gland Homogenates After Incubation with Cutaneous Bacteria. Thin-Layer Chromatography

Abstract: The effects of specific species of skin bacteria on human sebaceous gland lipids in vitro were analyzed. Isolated dissected sebaceous glands were pooled, homogenized, and sterilized, then incorporated into peptone-yeast extract medium and used as substrate for growth of Propionibacterium acnes, P. granulosum, and Staphylococcus epidermidis subgroup II. The sebaceous lipids were analyzed by thin-layer chromatography before and after bacterial growth. The most striking effect of bacteria on sebaceous gland lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 27 publications
1
43
0
2
Order By: Relevance
“…The observation of mass spectra from skin volatiles dominated by lactic and fatty acids is consistent with previous studies by GC-MS [29]. In particular, fatty acids beyond C12 are efficiently collected by solvent The structure is known to a reasonable degree of certainty, based on its exact mass and MS/MS spectrum interpretation.…”
Section: Resultssupporting
confidence: 89%
“…The observation of mass spectra from skin volatiles dominated by lactic and fatty acids is consistent with previous studies by GC-MS [29]. In particular, fatty acids beyond C12 are efficiently collected by solvent The structure is known to a reasonable degree of certainty, based on its exact mass and MS/MS spectrum interpretation.…”
Section: Resultssupporting
confidence: 89%
“…Enzymatic generation of free fatty acids from phospholipids 36 and cis-urocanic generation by degradation of histidine 37 are two of the most important endogenous mechanisms involved. Exogenous mechanisms such as lactate production in sweat glands 38 and microbial hydrolysis of sebaceous triglycerides 39 also may play a role in skin surface acidification.…”
Section: Skin Phmentioning
confidence: 99%
“…Behrendt and Green 27 found no significant differences between in skin pH in contralateral sites for vernix versus a water wipe (n ¼ 4) and suggested that the vernix layer (measured pH or 7.4) influenced skin acidification, as did maceration and desquamation. Puhvel et al 28 reported the hydrolysis of the triglycerides in sebum to fatty acids by skin surface bacteria. The triglycerides in vernix could be a source of acidic fatty acids at the skin surface, provided that conditions for hydrolysis are present.…”
Section: Skin Surface Adaptation and Acid Mantle Developmentmentioning
confidence: 99%